The Implementation of Hybrid Learning in Contextual English Language Learning - Risma Fahrul Amin; Zakaria Bintang Pamungkas (Hikamatzu | Journal of Multidisciplinary, 2024)
The objective of this study is to determine how to apply hybrid learning in contextual English language learning in high school. Hybrid learning means a measurable combination of in-person and distance learning, which means that some students may attend the meeting face-to-face, while others may attend the meeting online. This study offers some ways to apply hybrid learning in contextual English language learning. The implementation of hybrid learning in contextual English needs to be tested, observed, and evaluated to make it successful at the future